Multiple Capture Contributions In Charge Exchange Induced X-ray Spectra And Their Relevance To Astrophysical Applications - Otranto, Sebastian (2013)
In this work, we present theoretical line emission cross sections for Ar18+ and Ne10+ colliding on Ar for impact energies in the range 5 eV/amu-10 keV/amu which covers typical EBIT-traps as well as Solar Wind energies. The present analysis is performed by means of a 5-body classical trajectory Monte Carlo (CTMC) model which allows us to model the multiple capture contribution to the X-ray line emission spectra. Our results are contrasted to recent capture and line emission data from Berlin-EBIT, NIST and the University of Nevada Reno.